Surgical results of reduced port laparoscopic adrenalectomy using a multichannel port in comparison with conventional laparoscopic adrenalectomy - Jae Hyun Han (Asian Journal of Surgery, 2017)
Background: We introduced a modified laparoscopic technique, dual-incision laparoscopic adrenalectomy (DILA), using a newly designed multichannel trocar, and we evaluated its perioperative outcomes and operative costs and compared them to those of conventional laparoscopic adrenalectomy (CLA). Methods: We retrospectively reviewed the medical records of 127 patients who underwent CLA with four trocars or DILA with two trocars at Seoul St. Mary's Hospital, Seoul, Korea between October 2007 and September 2014. We analyzed the patients' surgical outcomes and perioperative morbidities. Results: DILA was performed in 45 patients and CLA in 82 patients. There were no significant differences in operative time (DILA: 77.1 ± 28.4 minutes vs. CLA: 76.6 ± 28.0 minutes, p = 0.595) or estimated blood loss during surgery (DILA: 150.0 ± 85.5 mL vs. CLA: 175.5 ± 50.5 mL, p = 0.697). There were no differences in postoperative hospital stay, visual analog scale pain score, or postoperative complication rates between the two groups. However, the operative cost was significantly lower in the DILA group (DILA 813,603 ± 48,600 Korean won vs. CLA 968,368 ± 56,456 Korean won, p < 0.001). Conclusion: This study demonstrated that DILA is a safe and feasible surgical approach for adrenal diseases. DILA may reduce the operative cost significantly compared with CLA.